Joint Segregation of High Glanding with Nectariless and Frego Bract in Cotton - Tcach, Mauricio Alfredo (2019)
There are mutant alleles in the genus Gossypium that increase its tolerance to insect pests. Among the traits that are effective against different insects, high glanding and nectariless increase cotton tolerance to lepidopteran insects, whereas frego bract suppresses the oviposition of the boll weevil, Anthonomus grandis Boheman. The objectives of this research were to transfer the high-glanding trait to frego-bract and nectariless plants. The genotypes used belonged to G. hirsutum: Guazuncho 3 INTA nectariless ne, SP 26 high glanding HG, and SP 47304 frego bract BF. Crosses between SP 26 HG/Guazuncho 3 INTA ne and SP 26 HG/SP 47304 BF and the F2 and F3 generations were obtained. For the combination of high glanding with frego bract, the frequency of individuals with both features varied from 6.4% in the F2 generations to 24.6% in the F3. For the other combination, high glanding with nectariless, the frequency of recombination was of 7.3% in the F2 and 11.8% in the F3. High glanding, nectariless, and frego bract are independently inherited traits in G. hirsutum. Therefore, it is possible to combine the high-glanding trait with frego bracts or nectariless in the same line.